The Characteristics of the Pelvic Floor Muscle Training Programs Used in Experimental Studies with Surface Electromyography in Non-Pregnant Women: A Systematic Review - Magdalena PIERNICKA; Barbara DUDA-BIERNACKA; Monika BŁUDNICKA; Anna SZUMILEWICZ (Tehran University of Medical Sciences, 2020)
Background: We aimed to characterize the pelvic floor muscle training (PFMT) programs for non-pregnant women used in the experimental studies with surface electromyography, based on the four training components: the frequency, intensity, time and type of exercises. Then, to characterize the study groups in which the PFMT programs were applied and the effectiveness of these programs. Methods: This is a review of 29 papers published in the years 1986-2019, available in PubMed, MEDLINE and SPORTDiscus with Full Text databases. We used keywords: "pelvic floor", "muscle training" and "EMG or electromyography". Results: Only in six articles all training components were characterized. The frequency was given in 17 papers, and on average it was 4 ± 2 (M ± SD) times a week. The intensity was described in nine reports, most often the maximal contraction of the pelvic floor muscles was recommended. Researchers conducted their interventions on average for 10 ± 5 weeks. The exercise sessions lasted 25' ± 10.49'. Type of exercises was specified in eleven papers and most often quick flicks were performed. In 90% of the studies the training programs were applied in women with pelvic floor muscle dysfunctions. In most works positive effects of PFMT were observed. No adverse outcomes of the use of electromyography were reported. Conclusion: The full training description should be presented in any scientific work, providing information on applied intensity, frequency, volume and type of pelvic floor muscle exercises to enable their replication and comparability between various interventions. It is important to pay more attention to preventive approach and the implementation of PFMT programs in healthy women. It is justified to use surface electromyography to support PFMT, regardless of health condition.